Phosphorous Sources, Consequences and Removal Techniques from Water - A Review - Rosalin Das (Progress in Chemical Science Research Vol. 9, 2023)
This review article comprehends the efficient techniques of removal of Phosphorous from domestic and industrial wastewater which are cost effective. The removal of excess phosphorous during wastewater treatment is vital for ensuring and protecting the ecosystem. Phosphorus is a critical nutrient for plant growth and is often a limiting factor in agricultural production. However, excess phosphorus in water can lead to environmental problems such as eutrophication and harmful algal blooms. There is a need for cost-effective and sustainable methods to remove excess phosphorus from water. This paper presents low-cost and environmentally friendly techniques for removing phosphorus from water. The removal of P from wastewater can be performed using physico-chemical methods, biological and Enhanced Biological Phosphorus Removal (EBPR) method, and/or combinations of both. The Physico chemical method deals with precipitation, coagulation, and flocculation. Most processes include precipitation, sorption and/or ion exchange mechanisms. Along with those Infiltration-percolation techniques, magnetic methods and biological methods are discussed. P removal rates are typically proportional to the mass of chemical added. In EBPR technique, Polyphosphate-accumulating organisms (PAO)s such as Candidatus Accumulibacter and Tetrasphaera were both important in all plants and contained together 24–70% of the total Phosphorus. The contribution of Tetrasphaera to the total P-removal was higher than that of Candidatus Accumulibacter. This low-cost technique has potential for use in rural and urban areas to address excess phosphorus in water, contributing to improved water quality and environmental sustainability.